Pemakaian Bahasa Persuasif Media Luar Ruang Selama Masa Pandemik Covid-19 di Dusun Nyangkringan, Kelurahan Bantul, Kecamatan Bantul, DIY - Rudi Ekasiswanto; Ridha Mashudi Wibowo (Faculty of Cultural Sciences, 2020)
The use of appropriate language by speakers has been proven to be able to convey messages clearly to the speech partners that they want, and it can even further change the behavior of the speech partners. This can be exemplified by the use of persuasive language in outdoor media. In order to get considerable attention, outdoor media installation is usually installed in a strategic location. The billboards that are installed, for example, are designed to be large and permanently installed within a certain period of time. The information displayed in billboards is arranged with the right diction, special sentence structure, and has a strong persuasive impact supported by an attractive design. Unfortunately, not all community members have the ability to make representative billboards. Community service activities in Nyangkringan village are aimed to develop two abilities, namely the ability to use language effectively and also to design attractive and informative-persuasive billboards. After receiving adequate guidance, the community service activity participants have been able to create billboards that are memorable and informative-persuasive. The installation of billboards at a later stage of the project indicates a significant change in behavior due to increased public awareness of the Covid-19 pandemic. It is hoped that with the abilities that they already have, in the future, the community service participants can make the necessary outdoor media according to their designation.====Pemakaian bahasa penutur secara tepat telah terbukti dapat menyampaikan pesan dengan jelas kepada mitra tutur yang dikehendakinya, bahkan lebih jauh lagi dapat mengubah perilaku mitra tutur. Hal ini dapat dicontohkan dengan pemakaian bahasa persuasif di media luar ruang. Agar dapat memperoleh perhatian yang cukup besar pemasangan media luar ruang biasanya dilakukan di lokasi yang strategis. Baliho yang dipasang, misalnya, didesain berukuran besar dan dipasang secara permanen dalam rentang waktu tertentu. Informasi yang dipajang di dalam baliho disusun dengan diksi yang tepat, struktur kalimat khusus, dan berdampak persuasif yang kuat didukung dengan desain yang menarik. Sayangnya, tidak semua anggota masyarakat memiliki kemampuan membuat baliho yang representatif. Aktivitas pengabdian kepada masyarakat di Dusun Nyangkringan kali ini ditujukan untuk mengembangkan dua kemampuan, yakni kemampuan menggunakan bahasa secara efektif dan mendesain baliho yang menarik dan informatif-persuasif. Setelah mendapat bimbingan yang memadai, peserta kegiatan pengabdian dapat mewujudkan baliho yang mengesankan dan informatif-persuasif. Pemasangan baliho pada tahap selanjutnya mengindikasikan perubahan perilaku yang signifikan atas meningkatnya kesadaran masyarakat terhadap pandemi Covid-19. Diharapkan dengan kemampuan yang telah dimiliki pada masa depan, para peserta pengabdian dapat membuat media luar ruang yang diperlukan sesuai dengan peruntukannya.